Nonsustained Atrial Fibrillation in Ischemic Stroke Patients and Stroke‐Free Controls From the Perspective of Stroke Pathophysiology. Issue 10 (October 2016) - Yetim, Ezgi; Topcuoglu, Mehmet Akif; Canpolat, Ugur; Gocmen, Rahsan; Oguz, Kader K.; Ozer, Necla; Aytemir, Kudret; Arsava, Ethem Murat
Abstract : Background: Short‐lasting (<30 s), nonsustained episodes of atrial fibrillation (NS‐AF) are considered a risk factor for future development of paroxysmal or persistent AF. Nonetheless, their causal role in stroke pathogenesis is currently unknown. In this study we determined the frequency of NS‐AF, together with the associated clinical and imaging features, in stroke‐free controls and ischemic stroke patients. Methods and Results: A total of 332 controls, ≥50 years of age and no prior history of stroke or AF, were evaluated with 24‐hour Holter monitoring for the presence of <30‐s‐long AF episodes. The demographic and cardiovascular features of this cohort, together with imaging finding on magnetic resonance imaging, were compared to a consecutive series of ≥50‐year‐old ischemic stroke patients without AF (n=498). The prevalence of NS‐AF was significantly higher among ischemic stroke patients in comparison to controls (37% versus 27%; P =0.002). In multivariable analyses, after adjustment for demographic and cardiovascular risk factors, patients with ischemic stroke were more likely to harbor NS‐AF episodes (odds ratio 1.43; 95% CI 1.01–2.02; P =0.041). The association between ischemic stroke and NS‐AF weakened when the analyses were restricted to cryptogenic stroke patients (odds ratio 1.31; 95% CI 0.82–2.08). No significant association was observed between the presence of chronic cortical infarcts and NS‐AF. Conclusions: Our study shows a higher prevalence of NS‐AF episodes in ischemic stroke patients in comparison to controls. Nonetheless, the lack of a stronger association with cryptogenic strokes and absence of a relationship with chronic cortical infarcts brings into question the causal influence of NS‐AF in the ischemic stroke setting.